Mathematical models to incorporate the in-plane flexibility of slabs in the seismic analysis of reinforced concrete buildings - Rodríguez, Miguel; López, Oscar (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Recent earthquake resistant codes recommend incorporating the in-plane flexibility of the slabs for the analysis of buildngs that have irregular plans in order to reach a more accurate determination of the design forces. For irregular section slabs such as the one-way T-section slabs of reinforced concrete, this paper identifies the main parameters that influence their in-plane flexibility. By means of parametric studies analytical expressions are proposed to determine the thickness of an equivalent flat slab so that its flexibility represents the one of the irregular section. For the typical one-wayT slab of height equal to 25 cm it 18 found that the equivalent thickness varies between 6 and 7 cm. The minimum number of plane finite elements to be incorporated in the analysis is detemined by means of parametric analysis. When the total number of the finite elements in all the slabs is greater than 16, the error is less than 7%. The proposed model to represent the in-plane flexibility of the slab is applied for the seismic analysis of a fourstory building; when the typical model of rigid diaphragm is used, the errors in the calculation of the forces at the resisting elements are as large as 25%.